Between- and within-biome resistance and resilience at the fynbos-forest ecotone, South Africa. (November 2019) - MacPherson, A James; Gillson, Lindsey; Hoffman, M Timm
In the Greater Cape Floristic Region (GCFR) of South Africa, afrotemperate forest islands persist within a broader landscape of Mediterranean-type fynbos shrubland. The co-existence of these contrasting vegetation types in the same climate space suggests interactions between broad-scale climatic parameters and localised variables (notably local disturbance regimes and catchment hydrology). In this study, palaeoecological data from a fynbos-forest boundary were used to assess the effects of interactions between changes in climate, fire and land use on vegetation dynamics and biome resilience at millennial timescales. Fossil pollen, spores and charcoal were extracted from radiocarbon-dated sediment cores to provide proxies for vegetation, hydrology, large herbivore abundance and fire. Constrained hierarchical clustering (CONISS) was applied to the fossil data to identify distinct vegetation assemblages in the palaeoecological record, and to further elucidate ecosystem trajectories through time. Regional palaeoenvironmental data are also referred to in inferring local and regional environmental changes. We expected to find shifts between fynbos and forest alternate stable states associated with changes in fire and rainfall. More specifically, we anticipated fynbos expansion during drier periods and/or those with more fire, and forest expansion during wetter and/or less fire prone periods. However, the fossil pollen data reveal remarkable stability of the fynbos-forest ecotone over the past 3000 years, despite significant changes in climate, fire and land-use. We found resilience of fynbos was enhanced through internal dynamics, namely, a shift from grassy, fire-prone fynbos in warmer, less seasonal time periods with less summer drought stress, to proteoid fynbos with less frequent fire during times of greater summer drought stress. The emergent properties of the respective fynbos types offset physiological advantages to forest species afforded by changes in the fire-free interval and abundant abiotic resource supply, inhibiting invasion of the former biome by the latter. We suggest these mechanisms require further investigation.